2015
DOI: 10.1021/acs.jmedchem.5b00092
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Exploration of Binding Site Flexibility in Mycobacterium tuberculosis BioA

Abstract: The PLP-dependent transaminase (BioA) of Mycobacterium tuberculosis and other pathogens that catalyzes the second step of biotin biosynthesis is a now well-validated target for antibacterial development. Fragment screening by differential scanning fluorimetry has been performed to discover new chemical scaffolds and promote optimization of existing inhibitors. Calorimetry confirms binding of six molecules with high ligand efficiency. Thermodynamic data identifies which molecules bind with the enthalpy driven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…29 Subsequent SAR-by-catalog of fragment hits resulted in the crystallographic and thermodynamic characterization of a series of inhibitors. 29,30 This study has shown that thermally destabilizing fragments can be inhibitors and that caution should be applied before rejecting negatively shifting fragments for further evaluation. Furthermore, it has been suggested that thermally destabilizing fragments may have an additional value in promoting a more rapid degradation of the target protein.…”
Section: Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…29 Subsequent SAR-by-catalog of fragment hits resulted in the crystallographic and thermodynamic characterization of a series of inhibitors. 29,30 This study has shown that thermally destabilizing fragments can be inhibitors and that caution should be applied before rejecting negatively shifting fragments for further evaluation. Furthermore, it has been suggested that thermally destabilizing fragments may have an additional value in promoting a more rapid degradation of the target protein.…”
Section: Results and Discussionmentioning
confidence: 89%
“…To our knowledge, only one fragment-based study selected both thermally stabilizing and destabilizing fragments against homodimeric Mycobacterium tuberculosis BioA (an aminotransferase that uses a pyridoxal 5-phosphate cofactor) for follow-up studies, although no rationale was given for considering thermally destabilizing fragments. 29,30 Only one out of the 12 destabilizing fragments from the original screen against BioA produced a structure by cocrystallization. 29 Subsequent SAR-by-catalog of fragment hits resulted in the crystallographic and thermodynamic characterization of a series of inhibitors.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several 3,4-bicyclic analogues ( 26–29 ) were inspired by the overlay of the acetylphenyl group of 6 or 12 with an inden-1-one moiety found and characterized in fragment screening (Figure 2B,C). 38 These compounds generally retained some biological activity, but only compound 26 with the identical inden-1-one of the original fragment hit improved upon the activity of 12 . A crystal structure of the complex with 26 (Table S1; PDB ID: 4XJO 36 ) was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Both 6 and 12 derive some potency from planar stacking between the amide bond of the piperazinyl carbonyl and Tyr25. 38 The amide plane is absent in piperidinyl analogues, but in the complex with 39 , the ring pucker permits a perfectly positioned C–H on C4 of the piperidine to donate a H-bond to the Tyr25 π -system, whereas the position of the chlorophenyl ring is consistent with the positioning of the same moiety in the complex with 12 . To rationalize the complete lack of activity for 40 , the analogous crystal structure of 6 was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of crystal structure of 4WYC revealed with hydrogen bonding interactions with nonpolar interaction like Trp398. The inhibitor is well associated with hydrophobic amino acids met61, Trp398, Trp64, Tyr407, and phe402 [10]. To validate the active site pocket the reference ligand was redocked and the docking score was found to be −6.032 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%